Collaborative Communication Patterns of Parents and Teachers in Strengthening Students’ Learning Motivation: A Case Study at SD Muhammadiyah 01 Kandang Panjang - Nafiaty, Ida; Egar, Ngasbun; Soedjono, Soedjono (Journal of Educational Sciences, 2025)
This study aims to explore the communication patterns between parents and teachers in fostering students’ learning motivation at SD Muhammadiyah 01 Kandang Panjang, Pekalongan City. Employing a qualitative case study approach, data were collected through interviews, observations, and documentation involving the principal, class teachers, and parents. The findings reveal three main communication channels: formal (monthly class parent association meetings), semi-formal (digital media such as WhatsApp), and informal (drop-off/pick-up interactions, personal phone calls, and home visits). These channels operate synergistically, enabling the timely exchange of information, strengthening emotional bonds, and enhancing parental involvement in the learning process. Effective communication was characterized by openness, message clarity, prompt feedback, and consistency, which contributed to increased student motivation, as indicated by improved participation, discipline, confidence, and active engagement in class. Challenges, including time constraints, low digital literacy, and limited parental participation, were addressed through flexible scheduling, home visits, and parental digital literacy training. The novelty of this study lies in the integration of three communication channels adapted to the sociocultural context of a faith-based elementary school. This model offers practical insights for developing adaptive school–home collaboration to foster students’ intrinsic and extrinsic motivation.